2014
DOI: 10.1039/c3ob42503g
|View full text |Cite
|
Sign up to set email alerts
|

A general synthetic strategy and the anti-proliferation properties on prostate cancer cell lines for natural phenylethanoid glycosides

Abstract: A general strategy for the synthesis of phenylethanoid glycosides (PhG) including echinacoside 1, acteoside 2, calceolarioside-A 3 and calceolarioside-B 4 is reported. The strategy features the application of low substrate concentration glycosylation and N-formyl morpholine modulated glycosylation methods for the construction of 1,2-trans β- and α-glycosidic bonds. The reported strategy does not invoke the use of the participatory acyl protecting function, which is incompatible with the ester function present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…In the Chinese Pharmacopoeia, components for controlling the quality of the raw and processed RG are catalpol and acteoside, respectively (Chinese Pharmacopoeia Commission, 2010). Acteoside also possesses various biological effects like catalpol, such as anti-oxidant (Esposito et al, 2010;Song and Sim, 2009), anti-bacterial (Pendota et al, 2013), anti-inflammatory (Alipieva et al, 2011;Marcial et al, 2014), anti-cancer activity (Mulani et al, 2014). Based on in vitro and in vivo pharmacodynamic research, catalpol is proved to display important and extensive pharmacological activities, including hypoglycemic (Deng et al, 2012;Li et al, 2014), anti-inflammatory (Akdemir et al, 2011;Kim et al, 2009), anti-spasmodic (Fleer andVerspohl, 2007) and anti-oxidant effects Huang et al, 2013), while acteoside is a phenylpropanoid glycoside characterized by caffeic acid and hydroxytyrosol bound to a glucose moiety through ester and glycosidic bonds, respectively, with a rhamnose unit linked to the glucose molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Chinese Pharmacopoeia, components for controlling the quality of the raw and processed RG are catalpol and acteoside, respectively (Chinese Pharmacopoeia Commission, 2010). Acteoside also possesses various biological effects like catalpol, such as anti-oxidant (Esposito et al, 2010;Song and Sim, 2009), anti-bacterial (Pendota et al, 2013), anti-inflammatory (Alipieva et al, 2011;Marcial et al, 2014), anti-cancer activity (Mulani et al, 2014). Based on in vitro and in vivo pharmacodynamic research, catalpol is proved to display important and extensive pharmacological activities, including hypoglycemic (Deng et al, 2012;Li et al, 2014), anti-inflammatory (Akdemir et al, 2011;Kim et al, 2009), anti-spasmodic (Fleer andVerspohl, 2007) and anti-oxidant effects Huang et al, 2013), while acteoside is a phenylpropanoid glycoside characterized by caffeic acid and hydroxytyrosol bound to a glucose moiety through ester and glycosidic bonds, respectively, with a rhamnose unit linked to the glucose molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Based on in vitro and in vivo pharmacodynamic research, catalpol is proved to display important and extensive pharmacological activities, including hypoglycemic (Deng et al, 2012;Li et al, 2014), anti-inflammatory (Akdemir et al, 2011;Kim et al, 2009), anti-spasmodic (Fleer and Verspohl, 2007) and anti-oxidant effects Huang et al, 2013), while acteoside is a phenylpropanoid glycoside characterized by caffeic acid and hydroxytyrosol bound to a glucose moiety through ester and glycosidic bonds, respectively, with a rhamnose unit linked to the glucose molecule. Acteoside also possesses various biological effects like catalpol, such as anti-oxidant (Esposito et al, 2010;Song and Sim, 2009), anti-bacterial (Pendota et al, 2013), anti-inflammatory (Alipieva et al, 2011;Marcial et al, 2014), anti-cancer activity (Mulani et al, 2014). Both catalpol and acteoside can significantly improve kidney function.…”
Section: Introductionmentioning
confidence: 99%
“… 51 , 52 It has been shown to possess versatile health promotional and disease preventive properties, including neural protection, hepatoprotection, and anti-inflammation, antifatigue, antisenescence, antidiabetes, and antitumor activities. 53 58 The best known and accepted bioactivity of Echinacoside is its antioxidative and ROS-scavenging action; 44 , 45 however, it has also been shown to cause oxidative DNA damages in cancer cells, with the underlying mechanisms remaining unclear. 58 In the present study, using a high-throughput in vitro screening assay, we found that Echinacoside effectively inhibited the MTH1-catalyzed enzymatic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The higher antiproliferative activity may be related to the α-Rha-(1→3)-Glc disaccharide unit and the 4-caffeoyl function in verbascoside. 127 The structure-cytotoxicity relationships among 14 PhGs compounds indicated that the fewer sugar units they have, the stronger activities they may have. Furthermore, the position of phenolic acid does not affect the activity.…”
Section: Anticancer Activitymentioning
confidence: 99%